Hubungan Disiplin Kerja dan Kompensasi Terhadap Kinerja Pegawai Di Badan Pengelolaan Pajak Dan Retribusi Daerah Kota Tanjungpinang - Novia Asiska Ramadani; Agus Hendrayady; Fitri Kurnianingsih (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The importance of managing staff performance in an organization or company, including aspects of discipline and compensation. Staff performance plays an important role in achieving the organization's goals. Work discipline and compensation relationships are very important factors in improving the quality of staff performance. Thus, the problem of non-discipline in the environment of an agency does not continue and can be solved. This study aims to determine the relationship of work discipline on employee performance of Badan Pengelolaan Pajak dan Retribusi Daerah Kota Tanjungpinang, the relationship of compensation on employee performance of Badan Pengelolaan Pajak dan Retribusi Daerah Kota Tanjungpinang, the relationship of work discipline and compensation on employee performance of Badan Pengelolaan Pajak dan Retribusi Kota Tanjungpinang. The research is a associate causality using quantitative methods. The sample of this study is 42 employee of Badan Pengelolaan Pajak dan Retribusi Daerah Kota Tanjungpinang. Data collection uses questionnaires while data analysis techniques use correlation analysis. Based on data analysis, it was concluded that there was no significant relationship between work discipline and staff performance, there was a significant link between staff performance compensation, and there was an important link between employment discipline, and staff performances compensation.